Efficacy of cetuximab-containing regimens in the treatment of recurrent/metastatic head and neck cancer after progression to immune checkpoint inhibitors. Issue 6 (10th June 2022) - Lai, Cheng-Lun; Chen, Tien-Hua; Chang, Peter Mu-Hsin; Tai, Shyh-Kuan; Chu, Pen-Yuan; Yang, Muh-Hwa
Abstract : Background: The antiepidermal growth factor receptor (EGFR) monoclonal antibody cetuximab and immune checkpoint inhibitors (ICIs) are the current front-line treatment for recurrent and metastatic head and neck squamous cell carcinoma (R/M HNSCC). However, understanding of the efficacy of cetuximab-containing regimens in patients who fail ICI treatments is limited. In this study, we present the efficacy of cetuximab-based regimens in heavily pretreated R/M HNSCC patients after progression to ICIs. Methods: This was a retrospective study that analyzed patients diagnosed with R/M HNSCC who progressed after ICIs and then received their first-time cetuximab-based regimens at Taipei Veterans General Hospital from January 2017 to December 2020. The response rate, overall survival, and progression-free survival were measured. Results: A total of 28 patients were included in this study. Most patients had received pembrolizumab as an ICI. The median duration of cetuximab-based regimens prescribed was 4.5 months. The objective response rate (ORR) was 32.1% (95% confidence interval [CI], 17.9%-50.6%), and the disease control rate (DCR) was 53.6% (95% CI, 42.4%-76.4%). The median overall survival and median progression-free survival were 9.1 months (95% CI, 1.3-16.8) and 2.9 months (95% CI, 2.2-3.5), respectively. The incidence of cetuximab-related adverse events was reported as 39.2%. Conclusion: A cetuximab-based regimen is still an effective and tolerable treatment for R/M HNSCC after progression on ICIs. Future prospective studies are needed to identify better treatments for previously ICI-treated or heavily treated R/M HNSCC patients.